Law Enforcement on Illegal Watershed Cultivation in Simalungun Regency - Siahaan, Richard; Zulyadi, Rizkan; Isnaini, Isnaini (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Law enforcement against illegal cultivation in the Watershed area is a significant challenge, especially in Simalungun Regency. This study aims to analyze the effectiveness of law enforcement against illegal cultivation, the obstacles faced, and the policies needed to overcome these problems. The research method used is a qualitative approach with data collection techniques through in-depth interviews, field observations, and document studies. The results of the study show that law enforcement efforts have been carried out through repressive approaches, such as joint operations and legal sanctions, as well as preventive approaches, such as socialization and education. However, its effectiveness is still hampered by limited resources, lack of coordination between agencies, resistance of local communities, and lack of accurate data related to watershed management. Some of the recommended strategic policies include capacity building for law enforcement officials, community empowerment through alternative livelihood programs, strengthening technology-based monitoring systems, and participatory approaches in policy formulation. The implementation of holistic and inclusive policies is expected to create a balance between environmental conservation and improving community welfare. This research emphasizes that sustainable watershed management requires synergy between legal, social, and technological approaches. Thus, law enforcement efforts are not only able to overcome legal problems but also build collective awareness to preserve the environment.